How to treat major depressive disorder with shorter-duration hypomanic episodes? A case report - Yao, Jiashu; Wang, Shenpang; Li, Yifei; Xu, Jiating; Ye, Ruihuan; Shen, Yuedi; Chen, Wei; Dai, Ning (Frontiers in Psychiatry, 2024)
Here we report on a case of a 61-year-old female patient with 7-year history of major depressive disorder with shorter-duration hypomanic episodes who was prescribed with antidepressants which turned out to be ineffective. After a COVID-19 infection, the patient's clinical presentation became sufficient for the diagnosis of bipolar disorder and she was consistently effective on a mood stabilizer and an atypical antipsychotic. The course of treatment in this case suggests bipolar disorder is not a binary disorder, but a continuous spectrum disorder. For patients suffering from major depressive disorder with shorter-duration hypomanic episodes, mood stabilizers and atypical antipsychotics are possibly more suitable than antidepressants.